Pathophysiological Features Resulting From Disruption of Synapse Function - oʻgʻli, Murodilloyev Ramziddin Mekhroj; qizi, Normamatova Maftuna Fozilov; Umirzokovna, Mamadiyarova Dilshoda (American Journal of Bioscience and Clinical Integrity, 2025)
This article analyzes the pathophysiological characteristics resulting from synaptic dysfunction. Changes in synaptic transmission affect inter-neuronal communication, leading to the development of various pathological conditions in the central and peripheral nervous systems. The study highlights the role of synapses in neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases, as well as in conditions like epilepsy, schizophrenia, and depression. Additionally, the article provides insights into molecular and cellular-level dysfunctions, neurotransmitter imbalances, and modern therapeutic approaches aimed at treating these pathologies.